Pelatihan Mubaligh Atau Da’i Pada IPNU (Ikatan Pelajar Nahdlatul Ulama) Dan IPPNU (Ikatan Pelajar Putri Nahdlatul Ulama) Kabupaten Lampung Tengah - M. Zainal Arifin; Andika Ari Saputra; Alwi Taufik; Yansen Alberth Reba; Wahyu Kusumaningtyas (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Mubaligh or Da'i are human beings who live in the mind of Islam, moving to exalt the religion of Allah with all the power they have as an obligation that must be carried out based on Allah's orders. Da'i are also called the subject of da'wah or called preachers who are engaged in da'wah according to their respective abilities. IPNU is one of the organizations in Indonesia and is an autonomous body of Nahdlatul Ulama, an organization that accommodates male students. This organization is called the Nahdlatul Ulama Student Association, abbreviated as IPNU which is educational, familial, social, and religious in nature. IPPNU is one of the organizations in Indonesia and is an autonomous body of Nahdlatul Ulama, an organization that accommodates female students. This organization is called the Nahdlatul Ulama Student Association, abbreviated as IPPNU which is educational, familial, social, and non-profit in nature. to increase understanding of religious values.